Divergent oxygen trends in ice-covered lakes driven by ice-cover decline and ecological memory - Joachim Jansen; Gesa A. Weyhenmeyer; Laura H. Härkönen; Andrew M. Paterson; Paul A. del Giorgio; Yves T. Prairie (Proceedings of the National Academy of Sciences, 2025)
Dissolved oxygen (DO) is an essential resource in ice-covered lakes, regulating water quality and biodiversity, including the survival of economically important fish species. Most of the world’s lakes seasonally freeze, often resulting in oxygen depletion as ice cover inhibits water column ventilation and snow cover limits photosynthesis while respiration continues. Widespread shortening of ice-cover duration in a warmer world might improve winter oxygenation, but this hypothesis remains untested. Here, we performed a systematic analysis of 6.6 million physical and chemical observations from 19,645 lakes in the Northern Hemisphere during 1960 to 2022. Contrary to expectations, under-ice DO trends ranged from significantly negative in small lakes (A surf <10 ha) (−0.14 ± 0.05 mg L −1 decade −1 ) to significantly positive in large lakes (≥10 4 ha) (0.11 ± 0.03 mg L −1 decade −1 ). This morphometric scaling emerged partly because ice-cover periods have shortened 2.2 times faster in large lakes compared to small lakes. Hierarchical modeling revealed that in smaller lakes, increasingly oxygen-depleted conditions in summer carried over to the ice-cover season, because fetch size limited wind-driven aeration in fall. As a result of this cross-seasonal ecological memory, under-ice hypoxic zones have expanded. Oxygen trended most negative in small eutrophic and humic lakes with high seasonal oxygen depletion rates. In larger lakes (≥10 3 ha), negligible summer deoxygenation, prolonged ventilation in fall, and shortening of the oxygen drawdown period in winter explained positive DO trends. However, in the vast majority of seasonally ice-covered lakes, which are small, continued climate warming is likely to exacerbate deoxygenation.